Effect of sorbitol at different concentrations on the functional properties of gelatin/carboxymethyl cellulose (CMC)/chitosan composite films - Bakry, N.F.; Isa, M.I.N.; Sarbon, N.M (Faculty of Food Science & Technology, UPM, 2024)
Non-Indexed Publication